Pengaruh Lokasi, Harga dan Promosi Terhadap Keputusan Penggunaan Layanan Jasa Laundry (Study Kasus Pada Konsumen Simply Fresh Laundry di Tembalang, Semarang) - Frederick Ido Hamonangan; Ari Pradhanawati; Bulan Prabawani (Jurnal Ilmu Administrasi Bisnis, 2017)
The decision to use services is an integration process that combines knowledge to evaluate two or more alternative behaviors and choose one of them. The decision-making process is a problem-solving approach where the process consists of five stages: analyzing needs and desires, seeking information, assessment and selection of alternative usage, use decisions and behavior after usage.This type of research is explanatory research design to data collection tool is questionnaire. This study used 100 respondents, consumer Stove Syndicate Cafe Semarang which has been a purchase more than five times . The sampling technique of this research is non probability sampling with accidental sampling approach. Test equipment instruments used are validity and reliability testing. Analysis of the data used is the correlation coefficient, determination coefficient, simple linear regression, t test, multiple linear regression, and F test.The results of this study show that under all partially independent variables, location variables (X1) affect the decision of the use of laundry service (Y) of 21.6%, price (X2) affect the decision of the use of laundry service (Y) of 4.3 %, and promotion (X3) affect the decision of use of laundry service (Y) equal to 51,1%. Simultaneously, location, price and promotion of contributing influence on the decision of the use of laundry service by 37,8%.Based on the result of this research, researcher suggest that Simply Fresh Laundry improve service quality, service addition, quality of service result which acceptable to consumer. This is done so Simply Fresh Laundry becomes a priority in choosing laundry services. Out to location, price, and promotion factors, there are still other factors that can influence service decision making.